Managing Pedagogical Efficiency Through TPACK Framework in Digital Learning - Arafat, Mudassir (2022)
Modern-day twenty-first-century education is now being constructed around the pillars of a framework that supports and dwells on Information and Communication Technology in the learning process. Nowadays, teachers are supposed to develop a pedagogical approach that integrates and blends with technology in learning. An appropriate structure of educational practice can motivate students' critical design, creativity as well as thinking skills. As seen in recent times the global Pandemic Covid-19 forced almost all learning institutions and the learning process to make extensive use of digital media, digital channels, online or virtual learning teleconferencing, mobile cellular technology, and any digital learning resource that could aid the outside the classroom form of learning. There are numerous digital learning applications in the form of computers or mobile devices that can be utilized for teaching and learning. Digital Learning primarily was designed to make learning easy & interactive but needs digital tools to exercise it. However, it is often seen many digital learning tools are way complex and need special training, hence making the teacher find it more complicated and often adapt to not practice it in their pedagogical approach. TPACK is a framework that highlights the labyrinth involved with the adoption of a particular digital learning tool and its use between the three basic components of knowledge (technology, pedagogy, and content). This particular article takes a deeper dive into the TPACK framework and how essential it is to integrate technology into education with ease. This article further helps in understanding how knowledge transfer works in a pedagogy. The article concludes with the variety of scientific works of literature reviewed. This article can hence acknowledge that to validate ICT in education TPAK framework is an important tool. It further helps in analyzing how teachers consider their knowledge zones crosses &limits to effectively teach and engage students with technology.